RELATIONSHIP BETWEEN GENDER AND STROKE RISK - Wilda Maulida Hikmah (Perhimpunan Kesehatan Holistik Indonesia, 2020)
Stroke is a blood circulation disorder in the brain that causes impaired brain function which can result in various effects on thebody. Symptoms of a stroke last more than 24 hours or cause death, in addition to causing death, a stroke will also have an impacton life. the impact of a stroke among others, the memory becomes impaired and there is a decline in memory, decreases thequality of life of the sufferer as well as family life and those around him, experiences a decrease in quality of life and physical andmental disabilities. The aim of the study was to determine the relationship between gender and stroke. This research design isquantitative with cross sectional design. The sample in this study amounted to 108 respondents. The test used is the chi squaretest. The results showed that there was a relationship between gender and stroke risk.